Postharvest behavior of mandarin fruits (Citrus reticulata Blanco) var. Arrayana: effect of different thermal treatments - Balaguera-López, Helber Enrique; Palacios O., Edgar Alfonso (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
Mandarin (Citrus reticulata Blanco) ‘Arrayana’ is one of the most important varieties in the country; however, postharvest losses are high as a result of the high perishability of the fruit. Therefore, the objective of this study was to evaluate the effect of different thermal treatments on the postharvest behavior of mandarin fruits var. Arrayana stored at 2ºC for 40 days. A completely randomized design was used, where the following thermal treatments were evaluated: (T1) control fruits, (T2) fruits treated with hot water at 50°C for 5 minutes, (T3) fruits treated with hot water at 53°C for 3 minutes, (T4) fruits subjected to intermittent warming with cycles of 8 days at 2°C + 1 day at 18°C and (T5) fruits subjected to intermittent warming with cycles of 12 days at 2°C + 1 day at 18°C. During storage there were no visible symptoms of chilling injury. At the end of storage, there were no statistical differences in sucrose, fructose and glucose, titratable acidity, citric, malic and ascorbic acids or total soluble solids. The intermittent warming was characterized by increasing fruit weight loss and respiratory rate, but it generated better fruit coloration because it induced a greater color change of the epidermis when there was a greater accumulation of total carotenoids and a low concentration of chlorophylls.